2020
DOI: 10.1002/smll.201907150
|View full text |Cite
|
Sign up to set email alerts
|

Active Delivery of VLPs Promotes Anti‐Tumor Activity in a Mouse Ovarian Tumor Model

Abstract: Virus‐like nanoparticles (VLPs) have been used as an attractive means in cancer immunotherapy because of their unique intrinsic immunostimulatory properties. However, for treating metastatic tumors in the peritoneal cavity, such as ovarian cancer, multiple injections of therapy are needed due to the large peritoneal space and fast excretion of therapy. Here, it is reported on the development of active VLP delivery vehicles for the treatment of peritoneal ovarian tumors using biocompatible Qβ VLPs‐loaded Mg‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 35 publications
0
59
0
Order By: Relevance
“…Active delivery in the peritoneal space of ovarian tumors was achieved, and the local distribution and retention of Q virus improved versus passive treatment. [216] Despite challenges, such as the potential Figure 4. Micro/nanorobot based delivery of biologics and genes.…”
Section: Biologicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Active delivery in the peritoneal space of ovarian tumors was achieved, and the local distribution and retention of Q virus improved versus passive treatment. [216] Despite challenges, such as the potential Figure 4. Micro/nanorobot based delivery of biologics and genes.…”
Section: Biologicsmentioning
confidence: 99%
“…Reproduced with permission. [ 216 ] Copyright 2020, Wiley. d) Sperm driven microrobot for heparin delivery capable of going against the flow.…”
Section: Targeted Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The self-driving of Mgmicromotor in the abdominal cavity improved the local distribution and retention of virus-like nanoparticles, and further enhanced immune stimulation, thereby increased the survival rate of tumor-bearing mice. [70] Recently, inspired by the in vivo endogenous reaction of catalase and active oxygen to decompose L-arginine into nitric oxide (NO) and L-citrulline, our group designed and prepared a kind of hyperbranched polyamide-L-arginine (HLA) nanomotors, which was propelled by NO bubble produced from L-arginine decomposition ( Figure 3B). In this self-propulsion system, the reactants and products were both harmless to the human body and even could be used as drugs.…”
Section: Bubble Propulsion Micro/nanomotorsmentioning
confidence: 99%
“…The results of fluorescence imaging and fluorescence quantification after 24 h of injection showed that virus‐like nanoparticles released from micromotor was concentrated in the tumor and major organs in the abdominal cavity. The self‐driving of Mg‐micromotor in the abdominal cavity improved the local distribution and retention of virus‐like nanoparticles, and further enhanced immune stimulation, thereby increased the survival rate of tumor‐bearing mice [70] …”
Section: Chemical Micro/nanomotorsmentioning
confidence: 99%